Improving Quality of Life Outcomes in Supported Accommodation for People with Intellectual Disability: What Makes a Difference? - Bigby, Christine; Beadle‐Brown, Julie (Journal of applied research in intellectual disabilities, 2018)
Background: The quality of life (QOL) of people with intellectual disability living in supported accommodation services is variable, influenced by many possible factors. Various frameworks have attempted to identify these factors without assigning value, direction of influence or relative impact on outcomes. Methods: A realist review of the literature aimed to expose different propositions about variables influencing QOL outcomes and review the strength of supporting evidence for these, to identify their relative influence. Evidence was reviewed for and against each of five clusters. Results: Evidence was strongest for the presence of staff practices (use of Active Support), front-line management practice (use of practice leadership), culture (enabling and motivating), human resources policies and practice (that support front-line leaders and recruitment of staff with the right values), adequate resources, and small, dispersed and homelike settings. Conclusions: The evidence informs policy and practice but in some clusters remains limited, warranting further research which measures outcomes on all QOL domains.